OC-030 Effective Stratification Of Hepatocellular Carcinoma Risk In Primary Biliary Cirrhosis: Results Of A Multi-centre International Study. (9th June 2014) - Trivedi, PJ; Lammers, W; van Buuren, H; Janssen, H; Invernizzi, P; Battezzati, PM; Floreani, A; Pares, A; Ponsioen, C; Corpechot, C; Poupon, R; Mayo, M; et al.
Abstract : Introduction: Hepatocellular carcinoma (HCC) is an important but infrequent outcome in primary biliary cirrhosis (PBC). Improved risk evaluation is an important goal for stratified surveillance. Methods: Risk-factor analysis of the 'Global PBC Study Group' comprising 15 centres across North America and Europe spanning >40-years follow-up was performed using Cox proportional hazards model, logistic regression and Kaplan-Meier estimates (SPSSv21). Results: Of 3546 patients with PBC (med. follow-up 8.6 yrs; IQR 4.4–14.1), 131 developed HCC. Excluding those who developed HCC within 12 months of PBC diagnosis (n = 23), median time to HCC was 12.7 yrs (6.9–16.8) and subsequent survival 1.1 yrs. (0.2–2.7). At diagnosis, factors associated with HCC development were male gender (adj. HR: 4.4;1.4–12.2, p = 0.014) and thrombocytopenia (adj. HR: 4.5;1.4–14.8, p = 0.012). Use of ursodeoxycholic acid per-se was not associated with future risk of HCC, but stratification of risk by biochemical response at 12 months was effective by Rotterdam (adj. HR: 8.9;2.1–37.3, P = 0.003), Paris-I (adj. HR: 7.6;2.0–29.0, p = 0.003) or Toronto criteria (HR: 5.6;1.6–18.8, P = 0.006). Five (4.6 vs. 0.2%) and 10-year (13%vs.1.9%) HCC incidence was significantly increased for biochemical non-responders (p = 2.2 × 10 –9 ), and by multivariate analysis non-response remained the only significant risk factor. Conclusion: Our uniquely powered cohort allows robust demonstration that 12-month biochemical non-response is associated with an increased risk of developing HCC in PBC. Routine surveillance in those achieving biochemical response is unlikely cost-effective. Disclosure of Interest: None Declared.